Conceptual Design of the Low-Cost Environmental Temperature Test Chamber System - Menyhárt, József; Szabolcsi, Róbert (International Journal of Engineering and Management Sciences, 2022)
Unmanned robots being remotely controlled or autonomous are spread worldwide and used in different purposes. Inhabited robots are brought very close to users and accessibility to these tools is very high, moreover, at very low costs. Regardless to emphasize the increasing popularity of these robots. However, any robot system being electrically driven and controlled has bottleneck in the amount of the electrical energy stored aboard in the battery packs. In other words, due to limited amount of the electrical energy available special issues related to use energy best way with maximum effectiveness are needed and considered. Additionally, the battery management system is needed to control the processes of the discharge and the charge ensuring technical data and parameters set by the manufacturer. This paper addresses robot applications in regions out of the calculated when special environmental testing is needed to confirm battery pack technical data. Among those of the environmental tests required the temperature test is in the focus of attention. The main idea and purpose of this paper is to set up new concept of the low-cost environmental temperature test chamber, to define its technical parameters and other properties needed for its preliminary design and prototype manufacturing.